2012
DOI: 10.1016/j.smallrumres.2011.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Novel microbiological system for antibiotic detection in ovine milk

Abstract: This article presents a microbiological system composed of a "BT" bioassay (Beta-8 lactams and Tetracyclines) and a "QS" bioassay (Quinolones and Sulfonamides). The 9 "BT" bioassay contains spores of Geobacillus stearothermophilus, bromocresol purple 10 and cloramphenicol in a culture medium (incubation time: 2.45 h), while the "QS" 11 bioassay uses spores of Bacillus subtilis, trifenyltetrazolium -toluidine blue and 12 trimethoprim in a suitable culture medium (incubation time: 5.5 h). The detection 13 capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…2010/37/EC established the maximum residue limits of fluoroquinolones for foodstuffs of animal origin, including milk (European Commission 2009), since these xenobiotic residues in milk could affect the health of milk consumers and increase antibiotic resistances (McManaman & Neville 2003). However, many of the commercially available screening tests are not sufficiently sensitive to detect many of the quinolones (Nagel et al 2012). Therefore, a special effort in the development of routine methods for detection of these antibiotics is advisable.…”
mentioning
confidence: 99%
“…2010/37/EC established the maximum residue limits of fluoroquinolones for foodstuffs of animal origin, including milk (European Commission 2009), since these xenobiotic residues in milk could affect the health of milk consumers and increase antibiotic resistances (McManaman & Neville 2003). However, many of the commercially available screening tests are not sufficiently sensitive to detect many of the quinolones (Nagel et al 2012). Therefore, a special effort in the development of routine methods for detection of these antibiotics is advisable.…”
mentioning
confidence: 99%
“…On the other hand, Montero et al (2005) detect a sensitivity higher than the MRLs both for Penicillin G and Amoxicillin using the Eclipse 100 ® method on ewe milk. In the paper by Nagel et al (2012), Penicillin G residues are found with a suitable limit of detection using two different bioassays, whereas Amoxicillin sensitivity was higher than the MRL for the bioassay based on the growth inhibition of Bacillus subtilis. As regard the use of rapid tests on ewe milk, satisfactory results have been obtained for Amoxicillin and Benzilpenicillin (Beltrán et al, 2013(Beltrán et al, , 2014.…”
Section: Resultsmentioning
confidence: 97%
“…This last concern is hypothesized to be linked to the microorganism used for the test, Geobacillus stearothermophilus var. calidolactis (Althaus et al, 2003) or to the particular traits of ewe milk which could interfere with the activity of the test (Comunian et al, 2010;Nagel et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the effectiveness of the analytical strategy currently applied in the sector for screening antibiotics in raw milk from sheep and goats, allows achieving el- of screening tests more sensitive to these substances would be convenient to increase the detection spectrum and, logically, minimize the risks stemming from the presence of these residues in milk. Thus, for example the application of the Bacillus subtilis bioassay would complement antibiotic coverage achieved by microbial inhibitor tests using G. stearothermophilus, detecting substances such as erythromycin, enrofloxacin and spiramycin at concentrations much closer to their respective MRLs (Nagel et al, 2012). Also, the periodic use of specific rapid methods for the detection of aminoglycosides and quinolones could be an alternative to increase the detection spectrum.…”
Section: Discussionmentioning
confidence: 99%